INFLUENCE OF COMPETITION AND SHADOW BANKING ON BANKING PROFITABILITY IN INDONESIA - Rifawati, Baetyka Nur (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Competition between banks can lead to various innovations and expansions in the banking sector that ultimately relate to the profitability that will be obtained by banks. Profitability is one of the important indicators commonly used to know the performance of banks in gaining profits in a country in a certain period. This study aims to analyze the influence of competition, shadow banking, and other determinant factors on the profitability of banks in Indonesia. The population studied in this study was conventional banks listed on the Indonesia Stock Exchange during the period 2014-2019. Sampling in this study using a purposive sampling method. Data analysis methods use multiple regressions. The results of the analysis in this study show that competition and company size has a positive and significant effect on the profitability of banks. Credit risk negatively and significantly affects bank profitability, while shadow banking has a positive but insignificant effect on bank profitability. Based on these results, it can be concluded that the level of competition, ownership of assets, and risk of bad credit greatly affect the profitability of the bank.